Avoiding state-space explosion in Model-Checker : M.A Thesis Information Technology : 60 48 01 - Bùi, Phi Điệp (ĐHCN, 2017)
Model-checking is a well-known technique for the program verification problem (i.e., checking that the program satisfies a given property). However, Model-checking su ↵ ers the state-space explosion problem. This is more visible in the the case of concurrent / parallel programs. Therefore, developing new e